Strategi Komunikasi Konselor dengan Pecandu Narkoba dalam Rehabilitasi Rawat Jalan : Studi Pada Bandan Narkotika Nasional Kabupaten Gayo Lues - Ayna Mardiah; Sabirin Sabirin; Hijrah Saputra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Drug abuse is a serious problem in society, especially in Gayo Lues, which not only harms individual users but also has a negative impact on the social environment. The National Narcotics Agency of Gayo Lues Regency (BNNK) is present as an institution that provides Outpatient services for people who are caught in drug abuse. The objective in this study is how the communication strategy of counselors with clients in outpatient assistance at the National Narcotics Agency of Gayo Lues Regency. This study uses a qualitative descriptive research type. This study focuses on interpersonal communication strategies. The results of the study revealed that the effectiveness of communication between counselors and drug addicts in outpatient rehabilitation at the National Narcotics Agency of Gayo Lues Regency is influenced by interpersonal communication strategies from a humanistic perspective which include openness, supportive attitudes, positive attitudes, and empathy.